Agroindustrial residues and energy crops for the production of hydrogen and poly-β-hydroxybutyrate via photofermentation. (September 2016) - Corneli, Elisa; Adessi, Alessandra; Dragoni, Federico; Ragaglini, Giorgio; Bonari, Enrico; De Philippis, Roberto
Highlights: Starch and sugars rich substrates led to higher H2 yields than fibrous substrates. Dark fermentation effluent of wheat bran allowed to accumulate 649 mL H2 L −1 . H2 production began only after propionic acid was depleted from the media. Mg 2+ and carbon deficiency can shift R. palustris from H2 to poly-β-hydroxybutyrate. Dark fermented ensiled olive pomace led to high poly-β-hydroxybutyrate accumulation. Abstract: The present study was aimed at assessing the biotransformation of dark fermented agroindustrial residues and energy crops for the production of hydrogen and poly-β-hydroxybutyrate (PHB), in lab-scale photofermentation. The investigation on novel substrates for photofermentation is needed in order to enlarge the range of sustainable feedstocks. Dark fermentation effluents of ensiled maize, ensiled giant reed, ensiled olive pomace, and wheat bran were inoculated with Rhodopseudomonas palustris CGA676, a mutant strain suitable for hydrogen production in ammonium-rich media. The highest hydrogen producing performances were observed in wheat bran and maize effluents (648.6 and 320.3 mL L −1, respectively), both characterized by high initial volatile fatty acids (VFAs) concentrations. Giant reed and olive pomace effluents led to poor hydrogen production due to low initial VFAs concentrations, as the original substrates are rich in fiber. The highest PHB content was accumulated in olive pomace effluent (11.53%TS), ascribable to magnesium deficiency.